Clinical and epidemiological characteristics of patients with end-stage chronic disease who were admitted in an emergency department - Amado-Tineo, Jose (2020)
Introduction. Patients with advanced chronic disease (cancer and non-cancer) often go to emergency services. Objectives. To determine terminal chronic disease in those admitted to emergency, reason for admission, treatment and destination, comparing cancer with non-cancer. Methods. Observational study in people over 18 year old admitted to the emergency department of a tertiary hospital. Instrument: Supportive and Palliative Care Indicators Tool. Statistical analysis: Chi-square and U Mann-Whitney tests, considering p <0.05. Results. Of 4925 admissions, 271 (5,5%) met criteria. 233 patients were analyzed, median age 77 years [28-99], female sex 59%. Cancer diagnosis 42%, dementia 23%, neurological sequelae 15%, liver cirrhosis 12% and another 8%. Reason for admission was 48% infection, 9% uncontrolled pain and 7% bleeding. Antibiotics were used in 48% of patients, opioids 12% (morphine and tramadol) and transfusions 9%; 8.6% of these patients received advanced life support (mechanical ventilation 5,6%, inotropic 4,7% and hemodialysis 0,8%). The median stay in the emergency room was 6 days [1-62]; 27% died, 32% were discharged and 42% were referred to another hospital department. The stay and reason for admission were similar in cancer and non-cancer (p>0,05), presenting older age and disease time in non-cancer patients (p<0,01). Conclusions. One of every 20 admissions to the emergency department evaluated corresponds to a chronic disease in the terminal phase (more frequent non-cancer), being the reasons for admission infections, pain and bleeding.